Analysis of the dynamics and identification of seasonal fluctuations in Ukrainian agricultural exports by type of transport - Totska, Olesia Leontiivna (University of Agronomic Sciences and Veterinary Medicine of Bucharest. Ceres Publishing House., 2024)
The purpose of this article is to analyse the dynamics and identify seasonal fluctuations in Ukraine's agricultural exports by type of transport from March 2022 to February 2024. The analysis uses a dashboard on the state of foreign trade in agricultural products. It contains a number of interactive diagrams on border crossings for nine types of goods (corn, wheat, sunflower oil, meal, rapeseed, soya beans, barley, sunflower seeds, soya oil) and four types of transport (ports, rail, road, ferries). The analysis shows that in March 2022 – February 2024, Ukrainian farmers exported an average of 4.768 million tonnes of products per month, of which 3.548 million tonnes were exported through ports, 837.9 thousand tonnes by rail, 321.2 thousand tonnes by road, and 61.6 thousand tonnes by ferries. The lowest volumes of exports of agricultural products were observed in March 2022, followed by a gradual increase. Exports by all types of transport are characterised by two waves of seasonality: growth (seasonality indices exceeding 100%) and decline (seasonality indices below 100%). For ports, these phases last in September-February and March-August; for rail transport, in August-February and March-July; for road transport, in July-November and December-June; and for ferries, in July-October and November-June. The seasonality of agricultural exports is related to the seasonality of their production, weather conditions, and the work of the customs services of Ukraine and the countries through which they are exported.

Метою цієї статті є проаналізувати динаміку та виявити сезонні коливання експорту агрокультур з України за типом транспорту з березня 2022 р. до лютого 2024 р. Для аналізу використано дашборд щодо стану зовнішньої торгівлі продуктами АПК. Він містить низку інтерактивних діаграм щодо перетину кордону за дев’ятьма видами товарів (кукурудза, пшениця, олія соняшникова, шроти, ріпак, соєві боби, ячмінь, насіння соняшнику, олія соєва) та чотирма типами транспорту (порти, залізничний транспорт, автомобільний транспорт, пороми). За результатами аналізу отримано, що упродовж березня 2022 р. – лютого 2024 р. українські аграрії щомісяця експортували в середньому 4,768 млн т продукції, з яких 3,548 млн т – через порти, 837,9 тис. т – залізничним транспортом, 321,2 тис. т – автомобільним транспортом, 61,6 тис. т – поромами. Найменші обсяги експорту продукції АПК спостерігалися в березні 2022 р., після чого відбулося поступове їх зростання. Для експорту за всіма типами транспорту характерні дві хвилі сезонності: зростання (індекси сезонності перевищують позначку 100 %) та спаду (індекси сезонності менші позначки 100 %). Для портів ці фази тривають у вересні-лютому та березні-серпні; залізничного транспорту – серпні-лютому та березні-липні; автомобільного транспорту – липні-листопаді та грудні-червні; поромів – липні-жовтні та листопаді-червні. Сезонність експорту аграрної продукції пов’язана із сезонністю їх виробництва, погодними умовами та роботою митних служб України і країн, через які здійснюється перевезення вантажів.
Keywords: exports; agricultural products; seasonal fluctuations; types of transport; Ukraine; експорт; аграрна продукція; сезонні коливання; типи транспорту; Україна